2019
DOI: 10.1177/1354816619846748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of tourist advertising to improve the competitiveness of destinations

Abstract: This study focuses on the evaluation of the tourist destination advertising effectiveness. The destination advertising response DAR model was used to analyze data on the effectiveness of destination promotional campaigns on visitor expenditure, in six trip facets: destination, accommodations, attractions, restaurants, events, and shopping. Independent sample t-tests were conducted to identify any differences in total destination spending among the groups of those visitors influenced for each trip facet. A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
(109 reference statements)
1
16
0
5
Order By: Relevance
“…We also found that for foreigners with different food neophilia/neophobia traits, message appeals had different effects on their willingness to eat Taiwanese delicacies. This is consistent with the finding of de Souza et al [ 28 ] that personality traits affect individuals’ attitudes toward, perceptions of and behavioural response regarding the content of the information appeal; that is, even with the same or similar messages, different personality traits lead to different attitudes, perceptions and behaviours. Therefore, we postulate that compared with the external environmental impact of information appeal, the internalized food neophilia/neophobia trait has a greater influence on individuals’ behaviour patterns and intentions, which is in line with the conclusions of Nezlek and Forestell [ 37 ], Ji et al [ 16 ] and Wolff and Larsen [ 7 ].…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that for foreigners with different food neophilia/neophobia traits, message appeals had different effects on their willingness to eat Taiwanese delicacies. This is consistent with the finding of de Souza et al [ 28 ] that personality traits affect individuals’ attitudes toward, perceptions of and behavioural response regarding the content of the information appeal; that is, even with the same or similar messages, different personality traits lead to different attitudes, perceptions and behaviours. Therefore, we postulate that compared with the external environmental impact of information appeal, the internalized food neophilia/neophobia trait has a greater influence on individuals’ behaviour patterns and intentions, which is in line with the conclusions of Nezlek and Forestell [ 37 ], Ji et al [ 16 ] and Wolff and Larsen [ 7 ].…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…In contrast, emotional appeal is an appeal to experience and emotion that expresses information in terms of senses, emotions and culture and emphasizes the creation of a beautiful perceptual atmosphere or emotion. According to de Souza et al [ 28 ], when promoting a product or service with which consumers are not familiar, rational appeal should be adopted because consumers’ interest in the product or service can be cultivated through facts or data. Hwang and Lin [ 29 ] found that providing product information (e.g., nutrition information) increased the willingness of American consumers to consume Asian food because nutrition information can reduce consumers’ uncertainty about choosing unfamiliar foods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is an effort to obtain sustained profitability, usually, beyond the industry average [30,31]. Cultural tourism industry competitiveness is a tool to measure the competitiveness of a destination's cultural tourism industry; it reflects the ability of a tourist destination to highlight its appeal to tourists and to provide them with better goods and services than other destinations [12].…”
Section: The Literature Related To the Cultural Tourism Industry Competitivenessmentioning
confidence: 99%
“…As a result, tourist destinations are increasingly trying to find new ways to gain a competitive advantage to attract more tourists [6][7][8][9]. Previous studies have identified different factors that are beneficial to building the competitive advantage of a destination, including problem recognition skills [10], branding [11], advertising [12], green initiatives [13] and service customization [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although destination competitiveness continues to attract tourism researchers' attention, minimal work has identified factors of destination competitiveness, especially environmental competitiveness, that contribute to tourism growth. Some prior empiricism has explored antecedents of destination competitiveness, such as tourist advertising (de Souza, Mendes‐Filho, & Buhalis, 2019), online reputation (Perles‐Ribes, Ramón‐Rodríguez, Moreno‐Izquierdo, & Such‐Devesa, 2019) and regional systems of innovation (Romão & Nijkamp, 2019) but did not address consequences of improving destination competitiveness. Tugcu (2014) notes that valuable core resources and well‐known tourist attractions, which are factors of destination competitiveness, may benefit destinations with inflow of tourists in the long run.…”
Section: Literaturementioning
confidence: 99%